IMPLIKATUR PERCAKAPAN WARGA RT 02 PERUMAHAN GRIYA ANUGERAH RESIDENCE - Bagus Tri Handoko (Jurnal Sastra Aksara, 2021)
Language is the most important tool for communication between humans. In other words, humans will be very dependent on a language and remember also that humans are social creatures, creatures who cannot live without other people. In this case, of course, between humans there will be an interaction (communication) for various purposes. The language used by humans is not a static language, but a language that is always evolving according to the needs of humans as users. This study examines the conversational implicatures contained in the conversations of residents of RT 02 Griya Anugerah Housing with the following problem formulation. 1) What is the form of implicature in the conversation of residents of RT 02 Griya Anugerah Residence Housing? and 2) what are the speaker's intentions and objectives contained in the conversations of residents of RT 02 Griya Anugerah Residence Housing? This research method uses a qualitative approach with the research subject of residents of RT 02 Griya Anugerah Residence Housing with the object of speech or conversation of residents of RT 02 Griya Anugerah Residence Housing. Data collection in this study was carried out directly at the location using the research subject and was carried out by observing notes. The results of this study are as follows. First, the implicature found in the conversations of residents of RT 02 Griya Anugerah Residence Housing, which is a combination of criticism and satire; (1) conventional, 2) general conversational implicatures, 3) specific conversational implicatures, 4) scaled implicatures, 5) statement implicatures. Based on the type of implicature, the speech conveyed by the subject mostly refers to an invitation. Invitation in speech serves to maintain the ethics of politeness in inviting certain parties to do something. Second, 2. The main function of implicatures in the conversation of residents of RT 02 Griya Anugerah Residence is so that the delivery of intent to comment on certain parties is more polite and does not hit the target. The implicature function found in this study also varies according to the type of implicature